Privacy in statistical databases UNESCO chair in data privacy, international conference, PSD 2010, Corfu, Greece, September 22-24, 2010 : proceedings - Domingo-Ferrer, Josep; bMagkos, Emmanouil (Lecture notes in computer science, 2011)
This book constitutes the proceedings of the International Conference on Privacy in Statistical Databases held in Corfu, Greece, in September 2010.